2002
DOI: 10.1109/20.996158
|View full text |Cite
|
Sign up to set email alerts
|

3-D transient eddy-current simulations using FI/sup 2/TD schemes with variable time-step selection

Abstract: A variable step size time integration method is used for transient eddy-current problems within the framework of finite integration implicit time-domain (FI 2 TD) formulations. The time-step selection is based on embedded Runge-Kutta methods, which provide an error with the difference of the two solutions of different order. This error allows a prediction of the next time step, for which different types of controller strategies are compared. The accuracy and efficiency of the method is investigated with variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…In this way, an formulation for eddy-current problems in the time domain is derived by the DGA, for unstructered and nonorthogonal dual grids, in which the primal grid is hexaedral. As far as the authors know, this is a major achievement with respect to previous results reported in literature [8], [9], in which eddy-current problems were discretized by DGA only over structured hexahedral grids. As shown by the proposed numerical analysis, the novel constitutive relations can lead to very accurate results at reduced computational costs, since they avoid the geometric discretization inaccuracy deriving from the use of orthogonal hexahedral grids [8], such as staircase effects, or from the use of structured hexahedral grids for modeling complex geometries [9].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In this way, an formulation for eddy-current problems in the time domain is derived by the DGA, for unstructered and nonorthogonal dual grids, in which the primal grid is hexaedral. As far as the authors know, this is a major achievement with respect to previous results reported in literature [8], [9], in which eddy-current problems were discretized by DGA only over structured hexahedral grids. As shown by the proposed numerical analysis, the novel constitutive relations can lead to very accurate results at reduced computational costs, since they avoid the geometric discretization inaccuracy deriving from the use of orthogonal hexahedral grids [8], such as staircase effects, or from the use of structured hexahedral grids for modeling complex geometries [9].…”
Section: Introductionmentioning
confidence: 86%
“…TIME INTEGRATION METHOD FOR DAE PROBLEM Systems (7) and (8) can be recast into the general form (14) where array denotes one of the unknown arrays or , and and are square matrices of dimension , being the number of primal edges in . Their definition can be easily evinced from (7) and (8). In our eddy-current problem, matrix is time invariant and independent of , the magnetic medium being linear.…”
Section: Discrete Constitutive Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use was refined in [4] and [5], the latter reference specifically adding results to increase the robustness of the scheme in practical simulations. In this method, however, an additional error-control scheme is required for the nonlinear algebraic systems of equations for each internal stage.…”
Section: Introductionmentioning
confidence: 99%
“…While already tested for linear magnetic problems in [5], these methods were originally designed to directly include the nonlinear Newton process, thus allowing to completely avoid additional nonlinear iterations within the error-controlled time marching process [2], [6].…”
Section: Introductionmentioning
confidence: 99%